A gender comparison of postobstructive injury in the rat kidney - Quinlan, Mark R. (2010)
Background/Aims: Unilateral ureteral obstruction (UUO) results in renal injury. Studies report increased injury indices in male rats following UUO. Our study examined whether this gender-based renal response to UUO was reflected in sustained differences following relief of obstruction. Methods: Adult male/female rats (200-400 g) were subjected to either sham surgery (S/RN) or UUO (UUO/RN). At 24 h, obstruc- tion was relieved and all animals underwent contralateral nephrectomy. Five days after initial surgery, animals were placed in metabolic cages and given water ad libitum for 24 h followed by a 24-hour period of complete water restriction. On day 7, animals were euthanized and samples harvested. Tubular injury, urinary volume/osmolality, creatinine clearance, plasma arginine vasopressin, renal medullary V2 receptor and aquaporin 2 (AQP2) expression were measured. Results: Male UUO/RN rats showed increased renal apoptotic injury and reduced creatinine clearance rates (glomerular filtration rate) vs. females. No gender-dependent differences were observed in urinary osmolality or concentrating ability. AQP2 expression increased post-obstruction. Conclusion: Increased injury in males following UUO remains manifest during early recovery after release of obstruction. Despite this, the grade of postobstructive diuresis is not significantly altered between sexes. This may reflect reduced glomerular filtration rate and elevated AQP2 in male rats.